Stan Mikols and Dale Snyder examining blueprints in Glass Fabrication department - Dow Chemical Company (1957)
General view of crew leader Stan Mikols (left) and Dale Snyder examining a blueprint used to manufacture a piece of glass in the Dow Chemical Company's Glass Fabrication department. Founded in 1925, the department was responsible for the fabrication and repair of specialty glass equipment used at the Company's plant in Midland, Michigan.
Keywords: Employees; Laboratories; Dow Chemical Company; Glass manufacture; Blueprints; Glassware; Mikols, Stan; Snyder, Dale